2014
DOI: 10.1007/s00148-014-0512-1
|View full text |Cite
|
Sign up to set email alerts
|

Muslims in France: identifying a discriminatory equilibrium

Abstract: We analyze the assimilation patterns of Muslim immigrants in Western countries with a unique identification strategy. Survey and experimental data collected in France in 2009 suggest that Muslims and rooted French are locked in a sub-optimal equilibrium whereby (i) rooted French exhibit taste-based discrimination against those they are able to identify as Muslims and (ii) Muslims perceive French institutions as systematically discriminatory against them. This equilibrium is sustained because Muslims, perceivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 51 publications
2
23
0
1
Order By: Relevance
“…As stated above, this is what was found by Adida et al (2014) who study the assimilation of Muslims in France. In their paper, they measure the cost of assimilation  by the taste-based discrimination of Muslims by the majority group.…”
Section: Star-shaped Networksupporting
confidence: 82%
See 2 more Smart Citations
“…As stated above, this is what was found by Adida et al (2014) who study the assimilation of Muslims in France. In their paper, they measure the cost of assimilation  by the taste-based discrimination of Muslims by the majority group.…”
Section: Star-shaped Networksupporting
confidence: 82%
“…Many European countries are concerned about the cultural integration and the (lack of ) assimilation of immigrants, that is whether the basic norms and values of the majority society are adopted by existing minority groups. 1 For example, recently, the European eastern countries such as Hungary or Poland have clearly expressed their reluctance to welcome Syrian refugees fleeing war, who are mostly Muslims, arguing that their integration and assimilation to the European culture will be very difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas we focus on studies on racial (or ethnic) discrimination conducted in America here (e.g., Butler 2014;Gell-Redman et al Forthcoming), scholars are increasingly conducting audit studies in other countries and to detect other types of biases (e.g., Adida, Laitin, and Valfort 2014;Hammarstedt 2012, 2013;Baert 2016;Neumark, Bank, and Van Nort 1995).…”
Section: Notesmentioning
confidence: 99%
“…They also felt that their needs have been less considered by state institutions as a consequence of the debates on the headscarves ban (EUMC, 2006). A survey conducted in France in 2009 revealed that Muslims in France perceived institutionalized discrimination against them in their context (Adida, Laitin, &Valfort, 2012).…”
Section: B Perceived Islamophobia and Discriminationmentioning
confidence: 99%